Implementation User-Centered Design in Agile Software Development: Systematic Literature Review - Mila Shania; Teguh Raharjo; Anita Nur Fitriani (Indonesian Journal of Multidisciplinary Science, 2023)
Agile is one of the commonly adopted methodologies in software development to achieve continuous development and meet customer satisfaction. The popularity of Agile has led to some research on the challenges faced when implemented in software development. The current era of user satisfaction is one of the success factors in product development using Agile. In this study, further research is carried out regarding the challenges in using Agile Software Development (ASD) and mapping solutions by combining it with the User-Centered Design (UCD) method. This research is presented using a systematic literature review method by reviewing 61 literatures. The results found that the combination of these two methods solved challenges related to the process implementation (16%) and in terms of product (18%), especially scope and requirement. These results provide practitioners and academicians with an understanding of ASD challenges and recommendations to deal with the challenges by combining with the UCD method.